Filling the knowledge gap regarding microbial occupational exposure assessment in waste water treatment plants - Riesenberger, Bruna (2024)
Funding Information: Authors gratefully acknowledge the FCT/MCTES national support through the UIDB/05608/2020; UIDP/05608/2020. This research was funded by national funds through FCT/MCTES/FSE/UE, 2023.01366.BD; UI/BD/153746/2022 and CE3C unit UIDB/00329/2020 (https://doi.org/10.54499/UIDB/00329/2020); UI/BD/151431/2021 (https://doi.org/10.54499/UI/BD/151431/2021) and Instituto Polit\u00E9cnico de Lisboa, national support through IPL/2022/InChildhealth/BI/12M; IPL/IDI&CA2023/FoodAIIEU_ESTeSL; IPL/IDI&CA2023/ASPRisk_ESTeSL; IPL/IDI&CA2023/ARAFSawmills_ESTeSL. Publisher Copyright: © 2024 by the authors.